2019
DOI: 10.1101/793000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypothalamic C2-domain protein involved in MC4R trafficking and control of energy balance

Abstract: 1 0 Objective: Rates of overweight and obesity epidemic have risen significantly in the past few 1 1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…RNAscope in situ hybridization was performed as previously described ( Domi et al, 2019 ; Gavini et al, 2020 ). The RNAscope assay was performed on formalin-fixed, paraffin-embedded (FFPE) tissue.…”
Section: Methodsmentioning
confidence: 99%
“…RNAscope in situ hybridization was performed as previously described ( Domi et al, 2019 ; Gavini et al, 2020 ). The RNAscope assay was performed on formalin-fixed, paraffin-embedded (FFPE) tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Using RNAscope, we previously showed the presence of C2CD5 mRNA in many parts of the brain, including high expression in the hypothalamus [9]. We also performed further high-resolution immunoelectron microscopy to visualize C2CD5 cellular localization at the protein level [9].…”
Section: Resultsmentioning
confidence: 99%
“…Using RNAscope, we previously showed the presence of C2CD5 mRNA in many parts of the brain, including high expression in the hypothalamus [9]. We also performed further high-resolution immunoelectron microscopy to visualize C2CD5 cellular localization at the protein level [9]. Using immunoprecipitation and mass spectrometry, we showed that C2CD5 is associated with components of mitochondrial membranes and other cellular membranes [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations